The Element of Deliberate Action in a Series of Actions on PRONA Program's Corruption Crime - Antonius Agung Ariyanto; Ira Alia Maerani (Universitas Islam Sultan Agung, 2021)
The purpose of this research is to analyze construction law panel of judges in deciding cases of corruption, qualifying extortion in the PRONA program. The research approach method used is a qualitative normative juridical approach. The legal construction built by the Panel of Judges in criminal cases of extortion qualification of corruption fulfills the provisions in Criminal Law, namely the Principles of Legality and culpability. The defendant was proven to have violated the law in the provisions charged by the public prosecutor, namely Act No. 31 of 1999 Jo Act No. 20 of 2001 and Article 55 paragraph (1) to 1 of the Criminal Code. The conclusion of this research is that the defendant was proven intentionally, at least knowing it as an intentional element, designing the Prona committee, determining Prona's fees, and issuing a “threat” letter to the applicant which should be free (with certain conditions). According to the Panel of Judges, such legal facts are sufficient to prove that the defendant was deliberately involved in the criminal act of corruption. It is recommended that in dealing with corruption cases with the same motive, in the future, the public prosecutor is more courageous in giving a single indictment. So that from the start, I was sure of the charges given, especially from the collection of materials and information through a catch operation.